2015
DOI: 10.3390/lubricants3020256
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-Hydrodynamic Analysis of a Plain Journal Bearing on the Basis of a New Mass Conserving Cavitation Algorithm

Abstract: Accurate prediction of cavitation is an important feature in hydrodynamic bearing modeling. Especially for thermo-hydrodynamic modeling, it is crucial to use a mass-conservative cavitation algorithm. This paper introduces a new mass-conserving Reynolds cavitation algorithm, which provides fast convergence and easy implementation in finite element models. The proposed algorithm is based on a variable transformation for both the pressure and mass fraction, which is presented in the form of a complementary condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…The Reynolds equation, which is a convection-diffusion type equation, is strongly convection dominated in highly loaded situations and will thus exhibit superious oscillations in the solution when solved using a typical Galerkin formulation. 13 The inconsistent (non-residual based) artificial diffusion method is one of the oldest and simplest methods as it directly adds an artificial diffusion term to the Reynolds equation in regions where the solution is strongly convection dominated. In Habchi et al, 8 it was shown that the solution was not significantly affected with the use of isotropic artificial diffusion.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…The Reynolds equation, which is a convection-diffusion type equation, is strongly convection dominated in highly loaded situations and will thus exhibit superious oscillations in the solution when solved using a typical Galerkin formulation. 13 The inconsistent (non-residual based) artificial diffusion method is one of the oldest and simplest methods as it directly adds an artificial diffusion term to the Reynolds equation in regions where the solution is strongly convection dominated. In Habchi et al, 8 it was shown that the solution was not significantly affected with the use of isotropic artificial diffusion.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…This approach, however, is not mass conservative and can therefore lead to inaccurate results, especially for thermal models where conservation of mass can be important [24]. Hence, in the third model, a mass conservative cavitation algorithm is used.…”
Section: Rotor Parametersmentioning
confidence: 99%
“…in which c f is a transformation coefficient that arises from a flow balance in the circumferential direction under the assumption of streamer cavitation; see Alakhramsing [24] for details. The physical pressure p can be calculated by:…”
Section: Rotor Parametersmentioning
confidence: 99%
See 2 more Smart Citations